The ? polymorph of 4-chloro-2-[(4-phenyl-thiazol-2-yl)hydrazonomethyl] phenol - Caliskan, Nezihe; Dag, Cemile; Yuksektepe, Cigdem; Cukurovali, Alaaddin; Murat, Ebru (Int Union Crystallography, 2006)
The title compound, C16H12ClN3OS, is polymorphic. In the alpha form, a dihedral angle of 13.3 (1)degrees exists between the approximately planar phenylthiazolehydrazine unit and the 4-chlorophenol ring. Intramolecular O-H center dot center dot center dot N hydrogen bonds are formed, and intermolecular N-H center dot center dot center dot O and C-H center dot center dot center dot N interactions generate R-2(2)(8) motifs that link the molecules into chains.